The importance of a contingency plan in the hospital pharmacy against the pandemic by the new coronavirus (Research, Society and Development, 2021)
This article aims to relate the role of hospital pharmacy in a pandemic scenario, such as the new coronavirus, and emphasize the importance of a contingency plan to face the impact caused by this pandemic in a hospital. From a theoretical review, where scientific works and literature on the subject were searched, in Scielo and Google Academic research platforms, it was possible to select and analyze contingency plans for hospital pharmacy proposed nationally and internationally, as well as articles, books, statistical data, statements, manuals, technical standards, among other materials that permeate this theme, correlating them with the attributions of a pharmacy service in health units. The results of the literature review corroborate the evidence of the need to develop a specific contingency plan for this scenario. Thus, it was concluded that it is up to the pharmacist to understand the care and management process to implement and execute a contingency plan in the hospital pharmacy specific for the COVID-19 pandemic. In order to fight the SARS-CoV-2 virus and mitigate its impact on the hospital environment and on society as a whole, ensuring the quality and safety of patients and employees.